Factual approach for tropical forest parameters measurement and monitoring: future option with a focus on synergetic use of airborne and terrestrial lidar technologies - Bazezew, Muluken N.; Hussin, Yousif A.; Kloosterman, Evert H.; M. Hasmadi, Ismail (Taylor and Francis Group, 2021)
Forest biomass and carbon are critical for ecological monitoring, and yet poorly modelled in complex ecosystems such as the tropical rainforests. To overcome this challenge incurred due to the complex biophysical properties of tropical forests, Airborne and Terrestrial LiDAR (Light Detection and Ranging) technologies have been used combinedly. Airborne LiDAR data ‘from above’ are largely restricted to analyses of lower canopy layer trees. Its combination with Terrestrial LiDAR allows the assessment of tree crowns under the upper canopy layer, thus opening up new possibilities for a more complete assessment of all the trees in a multi-layer stand. In this study, Airborne LiDAR was used for upper canopy tree measurements while Terrestrial LiDAR was complimented for lower canopy layer trees. The result showed that LiDAR-based tree measurements of DBH and height were highly accurate. We highly improved the accuracy of estimated above-ground biomass (AGB)/carbon from 87% of Terrestrial and 90% of Airborne LiDAR-based estimates to 97% through combining the use of the two technologies. This approach contributes to the development of efficient techniques for forest monitoring systems and bears the potential to extend the modelling options from remote sensing data to understory layer trees.